The History and Politics of Exhumation - Nash, Michael L. author. aut Link
XVII, 341 p. 4 illus.
Keywords: This book argues that a serious, scholarly study on exhumation is long overdue. Examining more well-known cases, such as that of Richard III, the Romanovs, and Tutankhamen, alongside the more obscure, Michael Nash explores the motivations beyond exhumation, from retribution to repatriation. Along the way, he explores the influence of Gothic fiction in the eighteenth century, the notoriety of the Ressurection Men in the nineteenth century, and the archeological heyday of the twentieth century.